2006
DOI: 10.1143/jpsj.75.074717
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Superconducting Cobalt Oxides NaxCoO2·yH2O

Abstract: Studies of the NMR Knight shift K of Na 0:3 CoO 2 . yH 2 O have been carried out in detail. The suppression of K by the occurrence of the superconductivity reported previously by the present authors in both magnetic field directions perpendicular and parallel to the c-axis has been confirmed, indicating that the Cooper pairs are in the singlet state. The anisotropy of the suppression amplitudes is consistent with the anisotropy of the hyperfine coupling constant A spin estimated from the K-plot. It has also be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…No evidence has been found in the search for the ferromagnetic fluctuations in the superconducting bilayer phase, as reported elsewhere in detail. The present result is consistent with the results of studies of the NMR Knight shift [4,5].…”
supporting
confidence: 93%
“…No evidence has been found in the search for the ferromagnetic fluctuations in the superconducting bilayer phase, as reported elsewhere in detail. The present result is consistent with the results of studies of the NMR Knight shift [4,5].…”
supporting
confidence: 93%
“…The magnetic and reentrant superconducting phases appear in some sets of samples for a duration after the synthesis [75,76,[80][81][82] although it is unclear what exactly occurs during this period. With increasing time after the synthesis, SC2, NS, and SC1 phases appear, in this order.…”
Section: Superconducting Phase Diagrammentioning
confidence: 99%
“…[2][3][4] We have carried out various kinds of experimental studies and revealed by measuring, in particular, the 59 Co-NMR Knight shifts that the spin-singlet pairing is realized in this system. [5][6][7] We have also found that the rate of the T c -suppression by non-magnetic impurities is small. 8) These results are simply explained by considering the s-wave superconducting pairs.…”
Section: Introductionmentioning
confidence: 58%